Protease‐activated receptor‐mediated platelet aggregation in acute coronary syndrome patients on potent P2Y12 inhibitors. Issue 3 (22nd May 2019) - Wadowski, Patricia P.; Pultar, Joseph; Weikert, Constantin; Eichelberger, Beate; Panzer, Benjamin; Huber, Kurt; Lang, Irene M.; Koppensteiner, Renate; Panzer, Simon; Gremmel, Thomas
Abstract: Background: Despite the increasing use of potent P2Y12 inhibitors, further atherothrombotic events still impair the prognosis of many acute coronary syndrome (ACS) patients. This may in part be attributable to intact platelet aggregation via the human thrombin receptors protease‐activated receptor (PAR)‐1 and PAR‐4. Objective: We studied PAR mediated platelet aggregation in ACS patients following percutaneous coronary intervention (PCI) with stent implantation in a cross‐sectional study. Methods: Platelet aggregation to ADP as well as to the PAR‐1 agonist SFLLRN and the PAR‐4 agonist AYPGKF was assessed by multiple electrode aggregometry in 194 ACS patients on dual antiplatelet therapy with aspirin and either prasugrel (n = 114) or ticagrelor (n = 80) 3 days after PCI. Results: Based on the consensus cutoff value, high on‐treatment residual platelet reactivity to ADP (HRPR ADP) was observed in only 2 prasugrel‐treated patients. Both patients with HRPR ADP had also a normal response to SFLLRN and AYPGKF. Among the 112 prasugrel‐treated patients with adequate P2Y12 inhibition, 50 patients (45%) still had a normal response to SFLLRN, and 70 patients (63%) still had a normal response to AYPGKF. Among the 80 ticagrelor‐treated patients with adequate P2Y12 inhibition, 25 patients (31%) still had a normal response to SFLLRN, and 50 (63%) still had a normal response to AYPGKF. Conclusion: Normal platelet aggregation via PAR‐1 and PAR‐4 is preserved in many patients with adequate P2Y12 inhibition by prasugrel and ticagrelor. The present findings may at least in part explain adverse ischemic events despite potent P2Y12 inhibition.